Indigenousity in the empowerment of construction laborers: A case study of the Indonesian Construction Labour Union (SBKI) Gunung Kidul - Maulana, Muhammad Husain (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2024)
This study aims to explore the role of local wisdom in the empowerment of construction laborers, focusing on the Indonesian Construction Labour Union (SBKI) in Gunung Kidul, using a qualitative approach. The findings show that these labor communities organically empower themselves through local traditions such as guys rukun and gotong royong, which not only build social solidarity but also strengthen labor organizations. Initiatives that emerge from within the community, both through labor rights advocacy and other empowerment activities, show that construction workers are able to utilize their local resources and potential to achieve welfare. This strong indigenousity within the community serves as important social capital in building organizational foundations, supporting advocacy processes, and empowering the community. The success of this empowerment initiative emphasizes the importance of respecting indigenousity in community development and demonstrates that communities can develop their own potential without the need for excessive external intervention. This indigenousity can ultimately serve as a model for other communities facing similar challenges. Keywords: Local wisdom, Labour union, Community empowerment   Penelitian ini bertujuan untuk mengeksplorasi peran indigenousitas dalam pemberdayaan buruh kuli bangunan, dengan fokus pada Serikat Buruh Konstruksi Indonesia (SBKI) di Gunung Kidul. dengan menggunakan pendekatan kualitatif. Temuan menunjukkan bahwa komunitas buruh ini secara organik memberdayakan diri melalui tradisi lokal seperti guyub rukun dan gotong royong, yang tidak hanya membangun solidaritas sosial tetapi juga memperkuat organisasi buruh. Inisiatif yang muncul dari dalam komunitas, baik melalui advokasi hak-hak buruh maupun aktivitas pemberdayaan lainnya, menunjukkan bahwa buruh kuli bangunan mampu memanfaatkan sumber daya dan potensi lokal mereka untuk mencapai kesejahteraan. Indigenousitas yang kokoh dalam komunitas ini berfungsi sebagai modal sosial yang penting dalam membangun fondasi organisasi, mendukung proses advokasi, dan memberdayakan komunitas. Keberhasilan inisiatif pemberdayaan ini menegaskan pentingnya penghargaan terhadap indigenousitas dalam pengembangan masyarakat dan menunjukkan bahwa komunitas dapat mengembangkan potensi mereka sendiri tanpa perlu intervensi eksternal yang berlebihan. Indigenousitas ini akhirnya dapat menjadi model bagi komunitas lain yang menghadapi tantangan serupa. Kata Kunci: Kearifan lokal, Serikat buruh, Pemberdayaan komunitas